Research progress of biomineralization for the diagnosis and treatment of malignant tumors - Wu, Yulu; Pan, Xun; Xie, Huixu; Que, Lin; Tang, Xiufa (Frontiers in Pharmacology, 2023)
Malignant tumors have long been a prominent subject of research in order to foster innovation and advancement in diagnostic and therapeutic modalities. However, the current clinical treatment of malignant tumors faces significant limitations. In light of recent advancements, the World Health Organization (WHO) officially designated malignant tumors as a chronic disease in 2006. Accordingly, maintaining the tumor in a stable state and minimizing its detrimental impact on the body emerges as a potentially advantageous approach to oncological treatment. One emerging strategy that has garnered substantial attention from the academic community is the construction of a biomineralized layer surrounding solid tumors for tumor blockade therapy. This innovative approach is regarded as safe, effective, and long-lasting. This review aims to provide a comprehensive summary of the advancements made in the utilization of biomineralization for the diagnosis and treatment of malignant tumors.